2013
DOI: 10.1007/s11743-013-1536-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Color Instability in a Liquid Laundry Detergent

Abstract: During reformulation of a liquid laundry detergent, an undesirable color change was observed: the normally blue color of the formulation was found to turn green when exposed to elevated temperatures during accelerated stability testing. Spectroscopic analysis revealed formation of a yellow substance, whose transmission spectrum combined with that of the blue dye to yield the observed green color. Sequential solid phase extraction using cation and anion exchange indicated the yellow substance was a base. Liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Discolouration of laundry detergents has been observed and investigated by many researchers. For example, oxidising phenolic antioxidant ingredients leads to yellowing and other ingredients that can lead to different colours (Missler et al, 2014). The other significance of colourants in detergent products is that they provide a special identity to the product.…”
Section: Colourantsmentioning
confidence: 99%
“…Discolouration of laundry detergents has been observed and investigated by many researchers. For example, oxidising phenolic antioxidant ingredients leads to yellowing and other ingredients that can lead to different colours (Missler et al, 2014). The other significance of colourants in detergent products is that they provide a special identity to the product.…”
Section: Colourantsmentioning
confidence: 99%
“…Film with good UV-barrier properties reported longer shelf life of packed detergent products due to the delay of active ingredients degradation, which will diminish the quality of the product. For example, propane-1,2-diol, which is a common liquid laundry detergent ingredient, is known to discolor upon exposure to sunlight [53] and to form a colored complex with iron (III) [54]. UV-vis spectrophotometer was used to evaluate the light transmittance of the fabricated films.…”
Section: Light Transparency Of Cellulose-reinforced Pva Biocomposite ...mentioning
confidence: 99%
“…Hand soap is included in personal care liquid products that are widely produced because it is more practical and has an attractive shape compared to solid soap. The parameters test such as viscosity, pH, the color of liquid soap, and foam stability produced after the formulation process greatly affect the physical properties of hand soap products [26][27][28][29][30][31]. Some previous research reported, the color agent for hand soap products uses congo red, methyl orange, and methylene blue.…”
Section: Introductionmentioning
confidence: 99%